Perancangan Dan Penyusunan Sistem Akuntansi Pada Online Shop The Zenzy Shoes - Anita Anita; Ellen Ellen (ConCEPt - Conference on Community Engagement Project, 2021)
Online Shop The Zenzy Shoes was founded in 2017, is engaged in shoes trading and is located at Ruko Ciptaland Blok Anggrek, Batam. The online shop has been around for 3 years, the records are still very simple, their every sales transaction is recorded in Microsoft Office Excel. The purpose of this research is to be able to design a reliable and accurate accounting recording system that has quality for users. The author designed a system using Microsoft Office Access to make it easier for users to enter transactions and display financial reports. The author designs the system according to the needs of MSMEs and makes forms of vendor data, customer data, goods data, purchases, sales and is equipped with a list of accounts, general journals, and a list of assets in order to present information on financial reports and after the system design is complete, the implementation continues with MSMEs to ensure that the system functions properly and there are no errors.